The relationship between race pattern and performance of elite 110m hurdlers - Shibayama, K.; Kijima, K.; Morioka, Y.; Sakurai, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
The present study aimed to define the phases of the 110m hurdle race and to clarify the relationship between the race pattern and performance of elite hurdlers. Seventy-six male hurdlers (groups: G1, 12.94-13.38 s, n = 24; G2, 13.40-13.68 s, n = 26; G3, 13.70-14.16 s, n = 26) participating in official competitions were videotaped using high-speed video cameras panning from start to finish (239.76 or 299.70 Hz). The landing step after hurdling was defined as the first step, and the take-off step was defined as the fourth step. The timing of each step and each interval (from touchdown on the landing step to the next landing step) were calculated. Intervals were divided into the acceleration phase (G1: from 1st to 2nd, G2 and G3: 1st), maximum velocity phase (G1: from 3rd to 5th, G2 and G3: from 2nd to 5th) and deceleration phase (G1, G2 and G3: from 6th to 9th). The results obtained were as follows: 1) Faster hurdlers sprinted with a shorter time and a larger mean interval velocity in all phases; 2) G1 had longer acceleration segments and larger acceleration from the acceleration phase to maximum velocity phase than G2 and G3 because of the larger increase in the frequency of the second step; however, deceleration from the maximum velocity phase to the deceleration phase showed no significant difference according to performance; and 3) the pattern of change in the mean interva3l velocity during the race was similar between G2 and G3. These results indicate that athletes in G2 need to improve their race pattern to achieve a larger acceleration in the 2nd interval by sprinting with a larger increase in the frequency of the second step. Improvement of the race pattern is less important for G3. Additionally, G2 and G3 need to improve their sprinting velocity to obtain a higher frequency at the fourth step.